The Efficacy and Safety of Biosimilars in Hidradenitis Suppurativa: A Comprehensive Review - Almukhadeb E; Almudimeegh A; Nagshabandi KN; Alsuwailem YL; Shadid A (Dove Medical Press, 2024)
Eman Almukhadeb,1 Almuntsrbellah Almudimeegh,1 Khalid Nabil Nagshabandi,1 Yousef Luay Alsuwailem,2 Asem Shadid3 1Department of Dermatology, College of Medicine, King Saud University, Riyadh, Saudi Arabia; 2Division of Dermatology, Ministry of National Guard Health Affairs, Riyadh, Saudi Arabia; 3Department of Dermatology, King Fahad Medical City, Riyadh, Saudi ArabiaCorrespondence: Khalid Nabil Nagshabandi, Department of Dermatology, College of Medicine, King Saud University, PJ7C+89Q, Riyadh, 12372, Saudi Arabia, Tel +966-582940888, Email khaloed23@gmail.comAbstract: Hidradenitis Suppurativa (HS), also known as Acne Inversa, is a chronic, recurrent inflammatory skin condition primarily affecting apocrine gland-bearing areas, such as the axilla and groin. Characterized by painful nodules, abscesses, and scarring, and has a profound psychological impact on patients. Current treatments aim to manage symptoms and prevent new lesions with a combination of non-pharmacological and pharmacological approaches. Emerging biosimilars, which replicate the efficacy and safety profiles of known biologics at a lower cost, offer new options for treating this debilitating cutaneous disorder. The review summarizes recent studies to explain the role of biosimilars in HS, emphasizing their potential to expand effective treatment options.Keywords: biologics, biosimilars, hidradenitis suppurativa, review